Are apolipoprotein E fragments a promising new therapeutic target for Alzheimer's disease?. (March 2022) - Vecchio, Filomena Lo; Bisceglia, Paola; Imbimbo, Bruno Pietro; Lozupone, Madia; Latino, Raffaela Rita; Resta, Emanuela; Leone, Maurizio; Solfrizzi, Vincenzo; Greco, Antonio; Daniele, Antonio; Watling, Mark; Panza, Francesco; et al.
Human apolipoprotein E (ApoE) is a 299-amino acid secreted glycoprotein that binds cholesterol and phospholipids. ApoE exists as three common isoforms (ApoE2, ApoE3, and ApoE4) and heterozygous carriers of the ε4 allele of the gene encoding ApoE ( APOE ) have a fourfold greater risk of developing Alzheimer's disease (AD). The enzymes thrombin, cathepsin D, α-chymotrypsin-like serine protease, and high-temperature requirement serine protease A1 are responsible for ApoE proteolytic processing resulting in bioactive C-terminal-truncated fragments that vary depending on ApoE isoforms, brain region, aging, and neural injury. The objectives of the present narrative review were to describe ApoE processing, discussing current hypotheses about the potential role of various ApoE fragments in AD pathophysiology, and reviewing the current development status of different anti-ApoE drugs. The exact mechanism by which APOE gene variants increase/decrease AD risk and the role of ApoE fragments in the deposition are not fully understood, but APOE is known to directly affect tau-mediated neurodegeneration. ApoE fragments co-localize with neurofibrillary tangles and amyloid β (Aβ) plaques, and may cause neurodegeneration. Among anti-ApoE approaches, a fascinating strategy may be to therapeutically overexpress ApoE2 in APOE ε4/ε4 carriers through vector administration or liposomal delivery systems. Another approach involves reducing ApoE4 expression by intracerebroventricular antisense oligonucleotides that significantly decreased Aβ pathology in transgenic mice. Differences in the proteolytic processing of distinct ApoE isoforms and the use of ApoE fragments as mimetic peptides in AD treatment are also under investigation. Treatment with peptides that mimic the structural and biological properties of native ApoE may reduce Aβ deposition, tau hyperphosphorylation, and glial activation in mouse models of Aβ pathology. Alternative strategies involve the use of ApoE4 structure correctors, passive immunization to target a certain form of ApoE, conversion of the ApoE4 aminoacid sequence into that of ApoE3 or ApoE2, and inhibition of the ApoE-Aβ interaction.